The use of remote sensing techniques by Modis (MCD45A1) images using to identify and evaluate burned areas in the metropolitan region of Belo Horizonte - MG, Brazil - Fernandes, Luiza Cintra; Nero, Marcelo Antonio; Temba, Plínio da Costa; Elmiro, Marcos Antônio Timbó (Sustainability in Debate, 2020)
The study of fire burned areas is very important, since they corroborate with control measures, prevention and monitoring of fires. Forest fires causes numerous impacts, among them, there is biodiversity lost and human health prejudice. So, it is a problem of environmental sphere as well as a social and political sphere. A way of monitoring this is using remote sensing techniques. So the propose of the present article is to use the Modis product (MCD45A1) to identify and evaluated the burned areas in metropolitan region of Belo Horizonte, among the years of 2012 to 2016, which is validated with Landsat-8/OLI sensor data. With the use of Landsat data it is possible to define the size of the burned area with greater precision, but requiring technical operational knowledge and specialized technical staff for both, on the other side, Modis is easier to operate, and have direct application and higher availability. It was observed that the study area has high burned area occurrences, mainly in spring and winter. The results found here could be used for future studies to decrease the forest fires incidence in the region and thus preserve the biodiversity of important biomes present in it.